Does euro area membership affect the relation between GDP growth and public debt? - Christian Dreger; Hans-Eggert Reimers (European University Viadrina, Department of Business Administration and Economics, 2012)
We analyse the relationship between the debt to GDP ratio and real per capita GDP growth for the euro area members by distinguishing between periods of sustainable and non-sustainable debt. Thresholds are theory-based and depend on the macroeconomic framework. If the interest rate exceeds nominal output growth, primary budget surpluses are required to achieve a sustainable debt ratio. The negative impact of the debt to GDP ratio is particularly strong for non sustainable ratios and especially relevant for the euro area. This suggests that the participation in monetary union might entail an additional risk for its members.
Keywords: F43; O11; C23; 330; Euro area debt crisis; debt sustainability; Öffentliche Schulden; Nachhaltigkeit; Sozialprodukt; Wirtschaftswachstum; Europäische Wirtschafts- und Währungsunion; Eurozone